The Impact Of Professionalism And Lecturer Competency On Lecturer Performance In Indonesia - Ahmad Qurtubi (Journal on Education, 2023)
The findings of this research reveal that the Performance of tertiary institutions is greatly determined by the Performance of the professors, with the lecturers' Performance being primarily influenced by their professionalism and competence. This study's findings also demonstrate the importance of HR management in universities, as strong HR management may considerably improve the impact of lecturers' professionalism and competence on their Performance. Even if both universities have professional and highly competent professors, institutions with superior HR management often have more excellent lecturer performance than universities with inferior HR management.